Dynamic capabilities : history and an extension - Nooteboom, B. (Cambridge : Cambridge University Press, 2022)
The development of salient ideas and publications on dynamic capabilities is given, extended by ideas outside the literature of strategic management. Dynamic capability is presented as an interdisciplinary subject to which knowledge is central. Diversity of knowledge is treated in terms of cognitive distance, limited through organisational focus. To deal with diversity, development and uncertainty, evolutionary theory and the notion of entropy are used. The relation between individual and organisational knowledge is modelled with the notion of a script and linguistic ideas. The governance of collaborative relations for innovation is discussed, including trust, which are also dynamic capabilities.
Title from publisher's bibliographic system (viewed on 01 Aug 2022).
Keywords: Strategic planning; Organizational learning